Implementing Ethical AI : From Principles to AI Governance - Seppälä, Akseli (My University, 2021)
The widespread application of AI comes with high expectations of benefits for many domains, including healthcare, finance, education, and transport. However, there have been equally alarming predictions of discriminatory systems, biased decision-making, and privacy violations. This has sparked a public concern and discussion on applied AI ethics. Prior research on AI ethics has been highly theoretical and conceptual, focusing on creating ethical AI guidelines and frameworks, whereas the empirical research is still under-researched and poorly available. Therefore, this study aims to fill this gap between theory and practice by conceptualizing some of today’s ethical AI practices. This study was set out to examine how ethical AI principles are put into practice in organizations developing or deploying AI, and to find out what are the drivers of implementing ethical AI. Overall, 13 semi-structured expert interviews were conducted with 12 AI organizations, and the data was analyzed following the Gioia method. As a result of the analysis process, it can be concluded that ethical AI principles are implemented as governance, and AI design and development practices, as well as knowledge management and stakeholder communication activities. As for the drivers, the ethical AI practices are motivated by trust and risks, regulatory and stakeholder pressure, and business drivers. Furthermore, the identified individual ethical AI practices and drivers are discussed in this research. The findings indicate that AI organizations had implemented relatively similar ethical AI practices that were recommended by today’s AI guidelines and frameworks. Moreover, ethical AI practices were not purely considered important for ethical reasons. Instead, organizations were more motivated by the pragmatic drivers, such as regulatory requirements, stakeholder pressure, maintaining customer trust or managing risks.

Tekoälyn laajempi käyttöönotto mahdollistaa monia etuja eri toimialoilla, kuten terveydenhuollon, rahoituksen, koulutuksen ja liikenteen parissa. Tämä on kuitenkin nostanut esiin hälyttäviä ennusteita syrjivistä järjestelmistä, vinoutuneesta päätöksenteosta ja yksityisyyden loukkauksista. Nämä kaikki ovat herättäneet yleistä huolta ja keskustelua tekoälyn etiikasta. Aikaisempi tutkimus tekoälyn etiikasta on ollut erittäin teoreettista ja käsitteellistä, keskittyen lähinnä tekoälyn eettisten ohjeiden ja viitekehysten luomiseen, minkä takia empiirinen tutkimus näistä on edelleen vähäistä ja huonosti saatavilla. Tämän tutkimuksen tarkoituksena on täyttää tämä aukko teorian ja käytännön välillä käsitteellistämällä joitakin nykypäivän eettisen tekoälyn toimintatapoja ja käytänteitä. Tämä tutkimus lähti selvittämään, miten tekoälyn eettisiä periaatteita sovelletaan käytännössä tekoälyä kehittävissä ja käyttävissä organisaatioissa, ja mitkä ovat ajureita eettisen tekoälyn soveltamiselle. Kaiken kaikkiaan 13 puolistrukturoitua asiantuntijahaastattelua suoritettiin 12 tekoälyä hyödyntävän organisaation kanssa, ja näistä saatu data analysoitiin Gioia-menetelmällä. Analyysin tuloksena voidaan päätellä, että tekoälyn eettisiä periaatteita toteutetaan hallinto-, ja tekoälyn suunnittelu- ja kehittämiskäytänteinä, sekä osaamisen ja ymmärryksen kehittämisen ja sidosryhmien viestinnän keinoilla. Eettisen tekoälyn toimintatapojen ajureina toimivat taas luottamus ja riskit, regulaation ja sidosryhmien painostus, sekä liiketoiminnannalliset ajurit. Tässä tutkimuksessa käsitellään myös yksittäisiä eettisen tekoälyn toimintatapoja ja ajureita. Tulokset osoittavat, että tekoälyorganisaatiot olivat toteuttaneet suhteellisen samanlaisia eettisen tekoälyn toimintatapoja, joita nykyiset tekoälyn eettiset ohjeet ja viitekehykset suosittelevat. Eettisiä tekoälyn toimintatapoja ei kuitenkaan suoritettu puhtaasti eettisistä syistä. Sen sijaan organisaatioita motivoivat enemmän käytännölliset tekijät, kuten regulaatiovaatimukset, sidosryhmien paineet, asiakkaiden luottamuksen ylläpitäminen tai riskien hallinta.
Keywords: AI, artificial intelligence, ethical, ethics, principles, AI governance, practice, implementation, adoption, tekoäly, eettinen, etiikka, periaatteet, käytäntö, implementaatio, adoptio